Analysis of real-world health care costs among immunocompetent patients aged 50 years or older with herpes zoster in the United States. Issue 8 (3rd August 2017) - Meyers, Juliana L.; Madhwani, Shweta; Rausch, Debora; Candrilli, Sean D.; Krishnarajah, Girishanthy; Yan, Songkai
ABSTRACT: Few peer-reviewed publications present real-world United States (US) data describing resource utilization and costs associated with herpes zoster (HZ) and postherpetic neuralgia (PHN). The primary objective of this analysis (GSK study identifier: HO-14–14270) was to assess direct costs associated with HZ and PHN in the US using a retrospective managed care insurance claims database. Patients ≥ 50 y at HZ diagnosis were selected. Patients were excluded if they were immunocompromised before diagnosis or received an HZ vaccine at any time. A subsample of patients with PHN was identified. Each patient with HZ was matched to ≤ 4 controls without HZ based on age, sex, and health plan enrollment. Incremental differences in mean HZ-related costs ("incremental costs") were assessed overall and stratified by age. Multivariable regression models controlled for the effect of demographic characteristics, prediagnosis costs, and comorbidity burden on costs using a recycled predictions approach. Overall, 142, 519 patients with HZ (9, 470 patients [6.6%] had PHN) and 357, 907 matched controls without HZ were identified. Resource utilization was greater among patients with HZ than controls. After adjusting for demographic and clinical characteristics, annual incremental health care costs for HZ patients vs. controls were $1, 210 for patients aged 50–59 years, $1, 629 for those 60–64 years, $1, 876 for those 65–69 years, $2, 643 for those 70–79 years, and $3, 804 for those 80+ years; adjusted annual incremental costs among PHN patients vs. controls were $4, 670 for patients 50–59 years, $6, 133 for those 60–64 years, $6, 451 for those 65–69 years, $8, 548 for those 70–79 years, and $11, 147 for those 80+ years. HZ is associated with a significant cost burden, which increases with advancing patient age. Vaccination may reduce costs associated with HZ through case avoidance.